A study of primary school learners’ metacognitive awareness of second language listening comprehension - Yusnita Mohd Taib. (2008)
This study investigated young L2 listeners’ metacognitive awareness about listening comprehension and analysed the effectiveness of process-based discussions in developing students’ inetacognitive knolwedge. Data was obtained from ten 12-yearold ESL students through two introspective methods: individual retrospection and group interviews.